2019
DOI: 10.24059/olj.v23i4.2043
|View full text |Cite
|
Sign up to set email alerts
|

Instructor Perceptions of Quality Learning in MOOCs They Teach

Abstract: Included in the discussions regarding the instructional and learning value of massive open online courses (MOOCs) is the question of whether MOOC learners gain much value, if any at all, and has been a continuing debate since MOOCs began. Skeptics argue that MOOCs lack academic rigor and are superficial, while proponents praise them as addressing important global issues of educational access and affordability, providing pathways to more substantial learning opportunities. An important viewpoint in this convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, not all MOOC pedagogical models are valid. As shown in Figure 5, MOOCs conceived of under sustainable curricular approaches must develop pedagogical designs based on constructivism (cMOOC), where the student is the protagonist of his/her learning through active and collaborative methodologies [56,57]. We do not mean that an xMOOC, with teaching model focused on the transmission of information, could not work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all MOOC pedagogical models are valid. As shown in Figure 5, MOOCs conceived of under sustainable curricular approaches must develop pedagogical designs based on constructivism (cMOOC), where the student is the protagonist of his/her learning through active and collaborative methodologies [56,57]. We do not mean that an xMOOC, with teaching model focused on the transmission of information, could not work.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the specific context, in which students are starting with this type of training, a MOOC is needed that has the students as its core focus, rather than the transmission of information typical of the xMOOCs [59,60]. constructivism (cMOOC), where the student is the protagonist of his/her learning through active and collaborative methodologies [56,57]. We do not mean that an xMOOC, with teaching model focused on the transmission of information, could not work.…”
Section: Discussionmentioning
confidence: 99%
“…Asynchronous discussion forums serve as a platform to support the learning process of online students by allowing them to build and share knowledge with others. Regarding learning in MOOCs, several studies have revealed that instructors perceive the beneficial role of online discussion features in facilitating quality learning (e.g., Askeroth & Richardson, 2019). Asynchronous discussion platforms are usually designed to help students learn from others by not only providing a venue for communication and interaction among students and instructors but also by enhancing content delivery (Baglione & Nastanski, 2007).…”
Section: Learning In Asynchronous Discussion Forumsmentioning
confidence: 99%
“…The teacher should take the role of a facilitator that applies constructivism theory in the online learning environment through collaborative activities that supports learning outcomes (Robinson et al, 2017). Social constructivism emphasizes on collaboration, communication and interactions among students which can be implemented in the online learning environment by encouraging students to interact with peers in the process of knowledge construction (Askeroth & Richardson, 2019).…”
Section: Collaborative Learningmentioning
confidence: 99%